Spontaneous regression of herniated lumbar intervertebral disc - Yilmaz, Nebi; Kaya, Arzu; Ozgocmen, Salih; Kiris, Adem; Kocakoc, Ercan (My University, 2006)
The aim of this report is to describe the very rare condition, spontaneous regression of herniated lumbar intervertebral disc, and the results of clinical follow-up and imaging modalities. A 53-year-old housewife presented with a 1-month history of low back and right leg pain. She had severe pain in her right leg radiating from the buttock to the heel and weakness of the right foot plantar flexion (rated 4/5 by manual motor testing), and straight-leg raising test was positive at 45° on the right side. Magnetic resonance imaging (MRI) revealed a large para-median extruded intervertebral disc at the L5-S1 level. She was followed up with medical treatments and physiotherapy and rehabilitation intervention. Follow-up MRI after 18 months since initial presentation revealed that extruded intervertebral disc material was completely resolved. In conclusion, the regression of the disc correlated with clinical improvement and was illustrated in follow-up magnetic resonance imaging. The exact mechanism underlying this condition is still unclear. As in our case, extruded lumbar intervertebral disc herniations may spontaneously regress and non-surgical conservative treatments may be appropriate. © 2006 Asia Pacific League of Associations for Rheumatology.
Keywords: Disc regression; Extruded disc; Lumbar disc herniation; Magnetic resonance